High-velocity water vapor corrosion of Yb-silicate: Sprayed vs. sintered body. (15th March 2020) - Bakan, Emine; Kindelmann, Moritz; Kunz, Willy; Klemm, Hagen; Vaßen, Robert
Abstract: The water vapor corrosion of Yb-silicates is of interest to their application as environmental barrier coatings in gas turbine technology. In this study, densified samples from the Yb-silicate powder, as well as plasma-sprayed free-standing Yb-silicate coating were tested at a high-velocity steam rig ( T = 1400 °C, v = 90 m/s, P H2O = 0.19 atm) for microstructural comparison. After the test, the measured weight losses of the coatings were larger than that of the densified sample. At the same time, the thicknesses of the corroded scales at the coating surfaces were found to be thicker than that of the sintered sample by a factor of two. Graphical abstract: Image, graphical abstract